ANALYSIS ON WHOLE BLOOD, SGOT, SGPT, AND TNF-a EXAMINATION IN PATIENTS WITH NON-DENGUE AND POSITIVE DENGUE FEVER (DF/DHF) - Anggraini, Rahayu; Nasronudin, Nasronudin (Institute of Topical Disease Universitas Airlangga, 2013)
Background: In Indonesia has four serotypes, the DEN-1, DEN-2, DEN-3 and DEN-4. The management of Dengue virus becomes difficult because the patients were infected with different clinical profiles depending on the serotypes and genotypes of infecting dengue virus. Consequently, the diagnosis and treatment becomes difficult. Aim: The purpose of this study was to identify the difference between the results of laboratory tests between non-dengue fever and positive dengue fever. Method: This study was an observational cross-sectional study. Fifteen samples were diagnosed with dengue fever and fifteen samples with negative dengue fever on NS1, IgM / IgG-anti-DHF strip test results. Laboratory tests comprising whole blood, SGOT, SGPT, and TNFa were first examined when the patient came to the hospital. The collected data were analyzed by Chi-Square test SPSS version 13 for Windows. Result: The results of the study in two groups regarding sex, age, days of fever, grade, hemoglobin levels, leukocytes count, platelet count, hematocrit percentage, SGOT levels, and TNFa level were not significantly different with p > 0.050, whereas the SGPT level in non-dengue increased 3 x of normal value of 66.7%, n = 10/15 and in positive dengue fever the SGPT level was within normal limits, found in 60%, n = 9/15, so there was significant difference with p = 0.022 (p < 0.05). Conclusion: in non-dengue SGOT and SGPT levels increased of 1–3 times the normal value. In positive dengue fever SGOT levels increased 1–3 x normal value, but SGPT levels was within normal value, so SGPT levels can be used as a predictive factor for distinguishing the two types of fever.